ZnO nanowire array-templated LbL self-assembled polyelectrolyte nanotube arrays and application for charged drug delivery - Yuan, Weiyong (2013)
Vertically oriented and robust polyelectrolyte nanotube arrays with high density, large area and high uniformity were successfully grown on substrates by a ZnO nanowire array-templated layer-by-layer (LbL) self-assembly approach for the first time, and were further used to deliver charged drugs, showing that they not only possess pH-responsive loading property, but also significantly enhance the loading capacity and sustained release time. This work could be extended to fabricate polyelectrolyte nanotube arrays with different polyelectrolyte combinations, including weak polyelectrolyte/weak polyelectrolyte, weak polyelectrolyte/strong polyelectrolyte and strong polyelectrolyte/strong polyelectrolyte. With the great versatility to use various substrates and building blocks, the polyelectrolyte nanotube arrays may have great potential for broad applications such as biosensor arrays, bioreactor arrays and optoelectronics.